The use of 3D power doppler ultrasound in the quantification of blood vessels in uterine fibroids: Feasibility and reproducibility. Issue 3 (11th August 2014) - Nieuwenhuis, Lotte L.; Betjes, Heleen E.; Hehenkamp, Wouter J.K.; Heymans, Martijn W.; Brolmann, Hans A.M.; Huirne, Judith A.F.
ABSTRACT Background To evaluate the interobserver agreement and discriminating value of three‐dimensional power Doppler ultrasound (3D PDUS) in patients with fibroids. Methods An observational prospective cohort study in 19 patients with fibroids. 3D PDUS was performed by one examiner and evaluated by three independent examiners in order to evaluate various vascular parameters: vascular index (VI), flow index, and vascular flow index of the fibroid, the vascular capsule and of its highest vascular area, using both manual and automatic contour modes. The intraclass correlation coefficient and discriminating values were calculated. The correlation between VI and volume was studied using Kendall's Tau test. Results In the manual contour mode, the VIs of the fibroid and of the vascular capsule had the highest interobserver agreements (intraclass correlation coefficients of 0.89 and 0.87, respectively). Both parameters seem to have good discriminating values, given the large range of these parameters between different fibroids, independent of their volume. The vascularity of the fibroid and capsule was related. VI was not related to the volume of the fibroid. Conclusions VI assessed using 3D PDUS is a reproducible parameter in the assessment of fibroid vascularization with discriminating abilities. Additional studies are needed to further evaluate its validity and clinical relevance. © 2014 Wiley Periodicals, Inc. J Clin Ultrasound43:171–178, 2015;